Immunopathological Study of Parasitic Cholangitis in Dolphins - Jáber Mohamad, José Raduán; Pérez, José; Zafra Leva,Rafael; Suárez Bonnet, Alejandro; Quesada Canales, Ildefonso Óscar; Fernández Rodríguez, Antonio Jesús; González Pérez, Jorge Francisco; Carrascosa Iruzubieta, Conrado Javier (Journal of Comparative Pathology, 2013)
This paper describes the immunophenotype of cellular inflammatory infiltrates in chronic cholangitis in six common dolphins (Delphinus delphis), four striped dolphins (Stenella coeruleoalba), three Atlantic spotted dolphins (Stenella frontalis) and one pygmy sperm whale (Kogia Breviceps) found stranded along the coasts of the Canary Islands (Spain). A panel of 5 antibodies previously tested in dolphins (anti-CD3, -IgG, -MHC class II, -S100 protein and -lysozyme) were used. The present work also reports cross reactivity with dolphin antigens of two antibodies not used to date in dolphins (anti-mouse iNOS and anti-mouse Foxp3). The most common type of cholangitis found was chronic granulomatous cholangitis, associated with the presence of the parasite Campula spp., or its eggs in bile ducts. The cellular composition of the hepatic inflammatory infiltrate associated to chronic parasitic cholangitis was closely similar to that found in the cortex of control lymph nodes, including the presence of S100(+) and MHC class II(+) dendritic-like cells in lymphoid follicles and interfollicular areas. Only occasional macrophages expressed iNOS, whereas Foxp3(+) lymphocytes were not found in any of the lesions described in the different types of cholangitis. 88 88 1 0,628 1,1 Q1 Q2 SCIE